Factors affecting transparency in the management of political violence in Bauchi State, Nigeria - Ilelah, Kabiru Bello; Ab Halim, Adlina; Ismail, Mohd Mahadee; Mohd Nor, Mohd Sabri (Human Resource Management Academic Research Society (HRMARS), 2023)
Transparency is critical for a modern democracy's efficient operation and the promotion of social well-being. Transparency ensures information is accessible. Without transparency, trust will be lacking between a government and those it governs. As a result, there would be social instability, such as political violence. Therefore, the study explored factors affecting transparency in managing political violence. The good governance theory is used as a guide. The study adopted a qualitative case study method. Purposive and snowball sampling techniques are used to identify 17 informants. A face-to-face interview through a Zoom online meeting was used to obtain the data. The data was analysed using thematic analysis with QSR Nvivo 12.0. The findings revealed that the government and its officials lack sincerity, which led to corruption in the management process of political violence. The finding also revealed that inadequate trust between the state government and the security agencies affects transparency practises. It was also demonstrated that lack of access to information on the management of political violence is another factor. From the findings, the research suggests that the government should be sincere and follow the principles of good governance in the management of political violence. Therefore, the research highlighted the key factors hindering transparency in the management of political violence.